Enantioselective Degradation of (2RS, 3RS)‐Paclobutrazol in Rat Liver Microsomes. Issue 5 (28th March 2015) - Wu, Shuchun; Yu, Miao; Zhang, Hu.; Han, Jianzhong; Qian, Mingrong
Abstract Paclobutrazol, with two stereogenic centers, but gives only (2R, 3R) and (2S, 3S)‐enantiomers because of steric‐hindrance effects, is an important plant growth regulator in agriculture and horticulture. Enantioselective degradation of paclobutrazol was investigated in rat liver microsomes in vitro. The degradation kinetics and the enantiomer fraction were determined using a Lux Cellulose‐1 chiral column on a reverse‐phase liquid chromatography–tandem mass spectrometry system. The t1/2 of (2R, 3R)‐paclobutrazol is 18.60 min, while the t1/2 of (2S, 3S)‐paclobutrazol is 10.93 min. Such consequences clearly indicated that the degradation of paclobutrazol in rat liver microsomes was stereoselective and the degradation rate of (2S, 3S)‐paclobutrazol was much faster than (2R, 3R)‐paclobutrazol. In addition, significant differences between the two enantiomers were also observed in enzyme kinetic parameters. The Vmax of (2S, 3S)‐paclobutrazol was more than 2‐fold of (2R, 3R)‐paclobutrazol and the Clint of (2S, 3S)‐paclobutrazol was higher than that of (2R, 3R)‐paclobutrazol after incubation in rat liver microsomes. These results may have potential implications for better environmental and ecological risk assessment for paclobutrazol. Chirality 27:344–348, 2015. © 2015 Wiley Periodicals, Inc.